2003
DOI: 10.1098/rstb.2002.1202
|View full text |Cite
|
Sign up to set email alerts
|

The enactive mind, or from actions to cognition: lessons from autism

Abstract: Normative-IQ individuals with autism are capable of solving explicit social cognitive problems at a level that is not matched by their ability to meet the demands of everyday social situations. The magnitude of this discrepancy is now being documented through newer techniques such as eye tracking, which allows us to see and measure how individuals with autism search for meaning when presented with naturalistic social scenes. This paper offers an approach to social cognitive development intended to address the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
356
4
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 693 publications
(395 citation statements)
references
References 114 publications
22
356
4
5
Order By: Relevance
“…Similar notions have been advanced in phenotypic studies contrasting the experiential development of children with autism and their typically-developing peers 30 , yet never heretofore demonstrated as having directly traceable genetic influence. Inherent to the classic twin design is the fact that interactions between genetic and unmeasured environmental factors will be subsumed under the category of additive genetic influence.…”
mentioning
confidence: 53%
“…Similar notions have been advanced in phenotypic studies contrasting the experiential development of children with autism and their typically-developing peers 30 , yet never heretofore demonstrated as having directly traceable genetic influence. Inherent to the classic twin design is the fact that interactions between genetic and unmeasured environmental factors will be subsumed under the category of additive genetic influence.…”
mentioning
confidence: 53%
“…It has therefore been proposed that perception of such movement cues is the initial step required for a whole host of socio-cognitive processes, including theory of mind, which enable rapid and appropriate responses to others (Klin, Jones, Schultz, & Volkmar, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The proposition that autistic symptoms might have roots in motor dysfunction has been made before in slightly different guises, by authors who have linked motor deficits to a range of cognitive and social impairments (Bo et al, 2016;Donnellan et al, 2013;Klin et al, 2003;Leary & Hill, 1996;McCleery et al, 2013;Mostofsky & Ewen, 2011;Rizzolatti & Fabbri-Destro, 2010) e and so in part we attempt here to build upon and extend this action perception deficit perspective and its neurocognitive consequences. Klin et al (2003) emphasised the grounding of social and cognitive processes in sensorimotor experience and suggested that this differed in autism, but did not strongly highlight the neurobiological architecture necessary for this 'grounding' or 'embodiment', nor base their account on neurobiological evidence from ASC.…”
mentioning
confidence: 99%
“…Klin et al (2003) emphasised the grounding of social and cognitive processes in sensorimotor experience and suggested that this differed in autism, but did not strongly highlight the neurobiological architecture necessary for this 'grounding' or 'embodiment', nor base their account on neurobiological evidence from ASC. A putative neurobiological substrate for embodied cognition and autistic symptoms was introduced in the original 'broken mirrors' hypothesis (Ramachandran & Oberman, 2006), which was later expanded by Rizzolatti and Fabbri-Destro (2010); these authors speak of impairments to mirror neuron systems, implying dysfunction of the link between perception and action.…”
mentioning
confidence: 99%
See 1 more Smart Citation